DECREASE IN MARKET VALUE OF A MOTOR VEHICLE - Marc Trömner (European Scientific Journal, ESJ, 2014)
Whereas in previous years the repair of accidental damages used to be connected with a remainder of accident traces, nowadays it is possible to repair even complicated accidental damages virtually without any trace or at least without defects by using today's conventional repair methods. However, it has to be noted that a vehicle with a repaired accidental damage realizes an inferior value on the market compared to an undamaged comparable vehicle. This decrease in market value can basically be explained by a change in purchase behavior influenced by possible doubts about the professional and proper repair or the apprehension of possible consequences of the accident. This change in vehicle value is therefore not so much caused by technical reasons but can be seen as a result of the purchase behavior and a changed market situation of the vehicle. Over the past few years a number of calculation methods have been introduced. As a rule, the calculation methods by Ruhkopf/Sahm, the Hamburg method, by Halbgewachs or by BVSK are common practice. In this connection it has to be noted that all calculation methods are subject to specific preconditions and lead only in certain cases to a realistic result. In general, it is necessary that the assessor evaluates the decrease in market value at his discretion as an expert. Knowledge of the market situation as well as a rough estimate of the decrease is, of course, a precondition. Previously, it was assumed - in particular by jurisdiction - that a vehicle only up to certain age or kilometrage (a maximum of 5 years, a maximum of 100,000 km) is subject to a corresponding decrease in market value. With regard to the usual life of vehicles today (average age of today's fleet of cars in Germany is approx. 7-8 years) and with regard to the reachable kilometrage of the vehicles (kilometrage of 350,000 km and more are quite possible) such limitations are in principle subjected to a critical discussion. The most important characteristic of a vehicle even if older than 8 years is nowadays always the lack of any accident history so that from the assessor's point of view a decrease in market value has always to be taken into consideration - also for vehicles with more than 100,000 km and older than 5 years. The corresponding decrease in market value can be estimated by assessors at their discretion having regard to all factors that influence value, in particular the scope of repair and the repair solution. Accurate calculation methods can only be used in few cases.